Buy‐Side Analysts and Earnings Conference Calls - JUNG, MICHAEL J.; WONG, M. H. FRANCO; ZHANG, X. FRANK (Journal of Accounting Research, 2018)
ABSTRACT Companies’ earnings conference calls are perceived to be venues for sell‐side equity analysts to ask management questions. In this study, we examine another important conference call participant—the buy‐side analyst—that has been underexplored in the literature due to data limitations. Using a large sample of transcripts, we identify 3,834 buy‐side analysts from 701 institutional investment firms who participated (i.e., asked a question) in 13,332 conference calls to examine the determinants and implications of their participation. Buy‐side analysts are more likely to participate when sell‐side analyst coverage is low and dispersion in sell‐side earnings forecasts is high, consistent with buy‐side analysts participating when a company's information environment is poor. Institutional investors trade more of a company's stock in the quarters in which their buy‐side analysts participate in the call. Finally, we find evidence that buy‐side analyst participation is associated with company‐level absolute changes in future stock price, trading volume, institutional ownership, and short interest.